PREDICTION OF ”RATE OF PENETRATION” (ROP) ON DRILLING FORMATION ”X” PROGNOSIS WELL ”YN2” BASED ON THE REPRESENTATIVE MODELLING FROM DRILLING FORMATION ”X’’ ACTUAL WELL ’’YN1’’ FIELD ’’IP’’ - KRT. Nur Suhascaryo; Sudarmoyo Sudarmoyo; Inrianto Pratomo (Universitas Pembangunan Nasional Veteran Yogayakarta, 2020)
Prediction value of the rate of penetration (ROP) in the drilling of the formation “X” well prognosis